2i(3-2i)+4-i=-3(3-2i)2i

Simple and best practice solution for 2i(3-2i)+4-i=-3(3-2i)2i equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2i(3-2i)+4-i=-3(3-2i)2i equation:



2i(3-2i)+4-i=-3(3-2i)2i
We move all terms to the left:
2i(3-2i)+4-i-(-3(3-2i)2i)=0
We add all the numbers together, and all the variables
2i(-2i+3)-i-(-3(-2i+3)2i)+4=0
We add all the numbers together, and all the variables
-1i+2i(-2i+3)-(-3(-2i+3)2i)+4=0
We multiply parentheses
-4i^2-1i+6i-(-3(-2i+3)2i)+4=0
We calculate terms in parentheses: -(-3(-2i+3)2i), so:
-3(-2i+3)2i
We multiply parentheses
12i^2-18i
Back to the equation:
-(12i^2-18i)
We add all the numbers together, and all the variables
-4i^2+5i-(12i^2-18i)+4=0
We get rid of parentheses
-4i^2-12i^2+5i+18i+4=0
We add all the numbers together, and all the variables
-16i^2+23i+4=0
a = -16; b = 23; c = +4;
Δ = b2-4ac
Δ = 232-4·(-16)·4
Δ = 785
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$i_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$i_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$i_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(23)-\sqrt{785}}{2*-16}=\frac{-23-\sqrt{785}}{-32} $
$i_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(23)+\sqrt{785}}{2*-16}=\frac{-23+\sqrt{785}}{-32} $

See similar equations:

| 2q–2q+q=18 | | 4x+8=17.2+5x | | 16m+4m–20m+3m–3=15 | | 13x-10=2(15)+12 | | z+3.7=8.9 | | 4x+8=17.2 | | n+17=4n-8 | | 61x+20x-20x=350+20x-20x | | 2(x12)-2x=3(x-2) | | 8x+32=4(x+5) | | ?x?x?=504 | | 700+1x=14 | | -5(4)+2y-1=3 | | y=-1/2*181.5 | | t+9=32 | | 5(x+7)=6(x-4) | | −0.55p−6=0.45p | | 7j+3j-6j=4 | | 2(6,5-4y)-4y=13 | | n+2=-10n+10n+6 | | 9-2x+4+3x=180 | | −0.55p−6=0.45 | | a–17=15 | | 43.61=X+.07x | | 8-1x=48x+3 | | 5(x-2)=3(2x1) | | 3x+7+4x=2x+8 | | 4^3x-6=16^x | | 24x+12=2(12x+6 | | 3(4x-1)+6=39 | | -9=-6v=3(v+2) | | 2w+8(w-3)=-4 |

Equations solver categories